2019
DOI: 10.1007/s12639-018-01082-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vaccine candidates purified from the adult ticks of Ornithodoros savignyi (Acari: Argasidae) and Hyalomma dromedarii (Acari: Ixodidae) against tick infestations

Abstract: Ticks cause anemia, toxicosis, growth delay, and transmit infectious diseases in animals and humans. The current study aimed to evaluate the immunoprophylactic properties of two vaccine candidates to develop vaccine against tick infestations. These two vaccine candidates were specific fraction from the adults of the soft tick Ornithodoros savignyi and cross-reactive fraction from the adults of the hard tick Hyalomma dromedarii. Both specific and cross-reactive fractions were isolated by Cyanogen Bromide-activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…For these reasons, alternative approaches to tick control have been suggested [ 18 ], of which vaccination or immunological control is regarded the most promising, environmentally friendly, and sustainable strategy. To date, numerous antigens have been reported to induce protection against Ixodid ticks [ 18 , 19 , 20 , 21 ] and less against Argasids [ 22 , 23 , 24 ]. Earlier, Willadsen [ 25 ] questioned whether combining antigens toward enhanced efficacy is a valid hypothesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, alternative approaches to tick control have been suggested [ 18 ], of which vaccination or immunological control is regarded the most promising, environmentally friendly, and sustainable strategy. To date, numerous antigens have been reported to induce protection against Ixodid ticks [ 18 , 19 , 20 , 21 ] and less against Argasids [ 22 , 23 , 24 ]. Earlier, Willadsen [ 25 ] questioned whether combining antigens toward enhanced efficacy is a valid hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, there are reasons for this slow progress which will not be addressed in this review. Therefore, it is not coincidental that to date only a few single vaccines against Argasids have been reported [ 22 , 23 , 24 ]. Nonetheless, tick researchers still aim to develop good vaccines which are able to induce a substantial humoral/or cell mediated protective immune responses in Argasid and Ixodid ticks.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a significant number of antigens have been identified that offer protection against these ticks. The range of effective immune responses against argasid ticks is notably narrower compared to those for ixodid ticks [ 162 , 163 , 164 , 165 ]. Trager’s early work highlighted that guinea pigs and rabbits could develop immune resistance to ixodid tick larvae after repeated exposure [ 166 ].…”
Section: Advances In Anti-tick Vaccinesmentioning
confidence: 99%
“…Recent efforts, like the Bovimune Ixovac ® vaccine, aim to boost Bm86 vaccine effectiveness, but their efficacy remains unverified against ticks [ 269 ]. Despite the success of the Bm86 vaccine against R. microplus ticks, its applicability to other tick species like Ixodes remains uncertain due to differing physiological and genetic factors [ 164 , 177 , 270 , 271 ]. While the Bm86 vaccine has proven effective, its inability to eliminate ticks entirely limits its standalone use, yet it significantly reduces the need for acaricides, lessening the economic burden of tick-borne diseases in livestock [ 272 , 273 ].…”
Section: Advances In Anti-tick Vaccinesmentioning
confidence: 99%
“…The prepared rabbit hyperimmune serum was defrosted and dialyzed for three days in a coupling buffer and then coupled to cyanogen bromide-activated Sepharose-4B (Sigma Aldrich) (2 mg/ml-swollen beads) according to the manufacturer's protocol. The C. parvum oocyst antigen was applied to the a nity column (Flex-Column, Kimble, USA) as described by Toaleb et al [59]. The bound fraction was eluted using the elution buffer.…”
Section: A Nity Puri Cation Of C Parvum Oocyst Antigenmentioning
confidence: 99%